2017
DOI: 10.3892/ijo.2017.3833
|View full text |Cite
|
Sign up to set email alerts
|

The protein arginine methyltransferase 5 promotes malignant phenotype of hepatocellular carcinoma cells and is associated with adverse patient outcomes after curative hepatectomy

Abstract: The prognosis of advanced hepatocellular carcinoma (HCC) is dismal. Novel molecular targets for diagnosis and therapy is urgently required. This study evaluated expression and functions of the protein arginine methyltransferase 5 (PRMT5) in HCC. Using HCC cell lines, the expression levels of PRMT5 mRNA were determined using the quantitative real-time reverse-transcription polymerase chain reaction, and the effect of a small interfering PRMT5-siRNA on cell phenotype was evaluated. Further, PRMT5 expression was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 31 publications
1
33
0
Order By: Relevance
“…Earlier clinicopathological analyses demonstrated that higher expression of PRMT5 was correlated with advanced tumor grade, presence of lymph node metastasis and poor prognosis (19,34,35). Consistent with previous studies by Zhang et al (17,18) and Shimizu et al (19), PRMT5 was significantly overexpressed in our HCC patient tissue samples, confirming the validity of these findings. Notably, our clinicopathological findings indicated the association among higher expression of PRMT5 with more frequent presence of microscopic hepatic invasion and higher AFP levels.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Earlier clinicopathological analyses demonstrated that higher expression of PRMT5 was correlated with advanced tumor grade, presence of lymph node metastasis and poor prognosis (19,34,35). Consistent with previous studies by Zhang et al (17,18) and Shimizu et al (19), PRMT5 was significantly overexpressed in our HCC patient tissue samples, confirming the validity of these findings. Notably, our clinicopathological findings indicated the association among higher expression of PRMT5 with more frequent presence of microscopic hepatic invasion and higher AFP levels.…”
Section: Discussionsupporting
confidence: 92%
“…Extensive analysis of PRMT5 in relation to human cancer has revealed its significant overexpression in various types of cancer, including breast (27) and gastric cancer (28), lymphoma (5,7,29) leukemia (7,30) and prostate cancer (31)(32)(33). Earlier clinicopathological analyses demonstrated that higher expression of PRMT5 was correlated with advanced tumor grade, presence of lymph node metastasis and poor prognosis (19,34,35). Consistent with previous studies by Zhang et al (17,18) and Shimizu et al (19), PRMT5 was significantly overexpressed in our HCC patient tissue samples, confirming the validity of these findings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations